Paparan Sampah Elektronik dan Organik pada Pekerja Informal: Laporan Kasus dengan Implikasi Kesehatan, Lingkungan, dan Keselamatan Kerja - Listina, osie; Subekti, Agung Tyas (Bhamada Occupational Health and Safety Environment Journal, 2025)
This report presents an anonymous case of an informal waste picker in an urban area who was referred to a healthcare facility with complaints suggestive of hazardous exposure: chronic cough, dermatitis on the hands, mild hearing impairment, and mild neurocognitive symptoms (fatigue, difficulty concentrating). The case highlights the complex health risks associated with waste management and the urgent need to integrate occupational safety, environmental protection, and recycling policies. The investigation revealed daily work involving manual separation of electronic waste (e-waste) and organic waste without adequate protective equipment, frequent open burning of waste, and a history of chemical contact. Management included symptomatic treatment, referral to occupational health services, preventive education, and policy recommendations for improving local recycling practices and protecting informal workers. This case underscores the urgent need to protect informal workers within waste management systems. Cross-sectoral policies are required to prevent long-term health and environmental impacts.